Come by the wind: Li Fan's story in Bunyun election - Li, Fan (Duisburger Arbeitspapiere Ostasienwissenschaften, 2004)
The article describes the experiences of the political scientist Li Fan with the first direct election in Buyun township, P.R. China. Li Fan gives details about the processes before and during the election and reviews the relevance of this election, that has been recognized worldwide. A short introduction by C. Göbel and A. Senz put this township election in a wider context of political reform in today’s China.
Zsfassung in dt. Sprache
Parallel als Druckausg. erschienen
Keywords: Li, Fan -- 1949-; China; Arbeitspapier; Graue Literatur